-6m-6=-6m-6

Simple and best practice solution for -6m-6=-6m-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6m-6=-6m-6 equation:


Simplifying
-6m + -6 = -6m + -6

Reorder the terms:
-6 + -6m = -6m + -6

Reorder the terms:
-6 + -6m = -6 + -6m

Add '6' to each side of the equation.
-6 + 6 + -6m = -6 + 6 + -6m

Combine like terms: -6 + 6 = 0
0 + -6m = -6 + 6 + -6m
-6m = -6 + 6 + -6m

Combine like terms: -6 + 6 = 0
-6m = 0 + -6m
-6m = -6m

Add '6m' to each side of the equation.
-6m + 6m = -6m + 6m

Combine like terms: -6m + 6m = 0
0 = -6m + 6m

Combine like terms: -6m + 6m = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 11x-(-2x-11)=7+8x | | 0.10(x+200.00)=55.00 | | (x+4)/(3x+12)=0 | | x+5(x-2)=14 | | -3.2a=-5.68 | | 5x-11x=42 | | 2e^8x=7 | | 0.10(x+200.10)=100.00 | | x^2+26x+60=0 | | 3-6r=15 | | 4p+13p=85 | | 4(x-1)-(5x-8)=2(4x-1)-3 | | 5-5=13x+3x | | 1/3b-3=b+9 | | 24/7*8 | | 1-1=2(1-h) | | 1-1=1(1-h) | | b+(-3)=8 | | 4v^2-48v-52=0 | | 32=1y-8-13y | | 8-4p=4p-(10p-4) | | 9+4x=3x+6 | | -7(t-8)-2(2t+1)=-12 | | 5-14=z/-7 | | 7/5*1 | | 5/6(x-9)= | | 8-2(x-3)=10 | | 3+2x+4-2x=7 | | 2(3w-5)+2(w)=150 | | 4-3t/6t-8 | | 13+20=10x+27 | | x^4+17x^2+70=0 |

Equations solver categories